SIFAT KIMIA DAN ORGANOLEPTIK TELUR ASIN MEDIA ABU SERABUT KELAPA DENGAN PERBEDAAN LAMA PENYIMPANAN - Onny Cahyasari; wikanastri hersoelistyorini; nurrahman nurrahman (Jurnal Pangan dan Gizi, 2019)
Eggs are easily damaged foodstuffs. Salting is one way to minimize damage and maintain storage. Salting generally uses NaCl salt for curing. In this study salting is done by utilizing the salt content of KCl in coconut fiber ash. This study aims to analyze the Total Volatile Nitrogen (TVN), rancidity (TBA) and organoleptic of salted eggs coconut fiber ash in during storage. This study used a Completely Randomized Design of One factor, with four different storage periods; 0 week storage, 1st week storage, 2nd week storage, and 3rd week storage were analyzed TVN (Total Volatile Nitrogen), TBA (Thiobarbituric Acid) and organoleptic properties (hedonic quality). Data on TVN and TBA were analyzed using ANOVA while organoleptic was analyzed using Friedmen test. The highest result of TVN at 3rd week was 1,902 mg / 100g and the highest TBA result also at 3rd week was 7.8 mg / kg of material. TVN and TBA results were noticeable differences during storage. The longer stored then the TVN and TBA levels will increase. The organoleptic test produces salted eggs with color, aroma, texture that were not significantly different during storage and taste that was getting salty during storage. Based on the results of organoleptic test, salted eggs of coconut fiber ash were still acceptable until 3rd week.